Peningkatan Potensi Pariwisata melalui Implementasi Konsep Family Fun Camp di Desa Petungsewu - Ariestadi, Dian; Ansyorie, Mohammad Musthofa Al; Ichwanto, M. Aris; Isnandar, Isnandar; Novianti, Novianti; Sholikah, Inka Pratiwi (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2024)
Petung Sewu Village, which is located in Dau District, Malang Regency, has cultural customs that are still very strong and have aboge community communities. In addition, the topography of this village is on the slopes of the sleeping princess mountain with an altitude of 700 meters above sea level. This village has 294.720 hectares of plantation area, 1.650 hectares of waqf land and 261.402 hectares of production forest. Petung Sewu Village, which is still beautiful with many trees, bamboo and a lot of local wisdom, is a suitable combination to introduce tourism in Petung Sewu Village further. Based on the potential of Petung Sewu Village, the Malang State University service team implemented a Family Fun Camp (FFC) as a Tourist Spot at the Petung Sewu Village Campground, Dau District. This service aims to develop the tourism potential of Petung Sewu Village to improve the surrounding community's economy. The stages of the procurement process include surveys and needs analysis, site measurement, design planning, presentation to the public, finalizing the design, evaluating the implementation of activities, and reporting. The indicator of the success of this community service is the formation of a new tourist spot that can become an icon of Petung Sewu Village and improve the economy of the surrounding community. Desa Petung Sewu yang berada di Kecamatan Dau, Kabupaten Malang, memiliki adat budaya yang masih sangat kental dan memiliki komunitas masyarakat aboge. Selain itu, topografi desa ini berada di lereng gunung putri tidur dengan ketinggian 700 meter di atas permukaan laut. Desa ini memiliki 294,720 Ha area perkebunan, 1,650 Ha tanah wakaf dan 261,402 Ha hutan produksi. Desa Petung Sewu yang masih asri dengan masih banyaknya pepohonan, bambu serta banyaknya kearifan lokal ini menjadi perpaduan yang cocok untuk lebih mengenalkan pariwisata di Desa Petung Sewu. Berdasarkan potensi Desa Petung Sewu, tim pengabdian Universitas Negeri Malang melakukan implementasi Family Fun Camp (FFC) Sebagai Spot Wisata di Bumi Perkemahan Desa Petung Sewu Kecamatan Dau. Pengabdian ini bertujuan untuk pengembangan potensi pariwisata Desa Petung Sewu sebagai salah satu upaya peningkatan ekonomi masyarakat sekitar. Tahapan proses pengadaan ini meliputi survey dan analisa kebutuhan, pengukuran lokasi, pembuatan desain rencana, pemaparan kepada masyarakat, finalisasi desain, evaluasi pelaksanaan kegiatan, dan pelaporan. Indikator keberhasilan dari pengabdian masyarakat ini berupa terbentuknya spot wisata baru yang dapat menjadi ikon Desa Petung Sewu dan peningkatan ekonomi masyarakat sekitar.